Chromatin remodeler Dmp18 regulates apoptosis by controlling H2Av incorporation in Drosophila imaginal disc development. - Feng, Y.; Zhang, Y.; Lin, Z.; Ye, X.; Lin, X.; Lv, L.; Lin, Y.; Sun, S.; Qi, Y.; Lin, X. (PLoS Genetics, 2022)
Programmed Cell Death (PCD) or apoptosis is a highly conserved biological process and plays essential roles both in the development and stress context. In Drosophila, expression of pro-apoptotic genes, including reaper (rpr), head involution defective (hid), grim, and sickle (skl), is sufficient to induce cell death. Here, we demonstrate that the chromatin remodeler Dmp18, the homolog of mammalian Znhit1, plays a crucial role in regulating apoptosis in eye and wing development. We showed that loss of Dmp18 disrupted eye and wing development, up-regulated transcription of pro-apoptotic genes, and induced apoptosis. Inhibition of apoptosis suppressed the eye defects caused by Dmp18 deletion. Furthermore, loss of Dmp18 disrupted H2Av incorporation into chromatin, promoted H3K4me3, but reduced H3K27me3 modifications on the TSS regions of pro-apoptotic genes. These results indicate that Dmp18 negatively regulates apoptosis by mediating H2Av incorporation and histone H3 modifications at pro-apoptotic gene loci for transcriptional regulation. Our study uncovers the role of Dmp18 in regulating apoptosis in Drosophila eye and wing development and provides insights into chromatin remodeling regulating apoptosis at the epigenetic levels.